2012
DOI: 10.1038/nature11716
|View full text |Cite
|
Sign up to set email alerts
|

RNAi triggered by specialized machinery silences developmental genes and retrotransposons

Abstract: RNAi is a conserved mechanism in which small interfering RNAs (siRNAs) guide the degradation of cognate RNAs, but also promote heterochromatin assembly at repetitive DNA elements such as centromeric repeats1,2. However, the full extent of RNAi functions and its endogenous targets have not been explored. Here we show that in the fission yeast Schizosaccharomyces pombe, RNAi and heterochromatin factors cooperate to silence diverse loci, including sexual differentiation genes, genes encoding transmembrane protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
204
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(228 citation statements)
references
References 32 publications
(45 reference statements)
16
204
0
Order By: Relevance
“…MTREC along with associated RNA-processing factors also has been implicated in RNAi-dependent assembly of heterochromatin domains on developmental genes and retrotransposons (10,11). To determine whether Dhp1 cooperates with MTREC to assemble RNAi-dependent HOODs, we introduced dhp1-2 into a strain carrying rrp6Δ that allows detection of HOODs under standard growth conditions (10).…”
Section: Dhp1 Affects the Assembly Of Heterochromatin Islands At Meioticmentioning
confidence: 99%
See 2 more Smart Citations
“…MTREC along with associated RNA-processing factors also has been implicated in RNAi-dependent assembly of heterochromatin domains on developmental genes and retrotransposons (10,11). To determine whether Dhp1 cooperates with MTREC to assemble RNAi-dependent HOODs, we introduced dhp1-2 into a strain carrying rrp6Δ that allows detection of HOODs under standard growth conditions (10).…”
Section: Dhp1 Affects the Assembly Of Heterochromatin Islands At Meioticmentioning
confidence: 99%
“…In particular, RNAi machinery is believed to function in the assembly of major constitutive heterochromatin domains coating centromeres, telomeres, and the mating type (mat) locus (7)(8)(9). RNAi-dependent mechanisms also assemble dynamically regulated facultative heterochromatin domains, hereafter referred to as "HOODs", at discrete sites across the genome, including at developmental genes and retrotransposons (10). HOOD assembly is triggered by the specialized nuclear RNA processing and surveillance complex Mtl1-Red1 core (MTREC) and/or associated mRNA 3′-end processing activities, including the canonical poly (A) polymerase Pla1 and the poly(A)-binding protein Pab2, to direct transcripts into RNA degradation pathways and target heterochromatin assembly (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Independently of heterochromatin assembly, RNAi silences meiotic genes during vegetative growth 10,11 . The untimely expression of gametogenic genes, which has been found to occur in tumors in humans 12,13 and to induce tumorigenesis in Drosophila 14 , might be linked to aneuploidy observed in cancer cells.…”
mentioning
confidence: 99%
“…The YTH-family protein Mmi1 promotes degradation of meiotic gene transcripts by RNAi and the nuclear exosome 10,11,1518 . Comparing the expression profiles of cells lacking RNAi components or Mmi1 revealed that a majority of the meiotic genes that were upregulated in ago1 ∆ or dcr1 ∆ RNAi mutants (85 out of 152) were also upregulated in mmi1 ∆ (Fig.…”
mentioning
confidence: 99%